2023
DOI: 10.1136/openhrt-2022-002157
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre experience with Optimus balloon-expandable cobalt–chromium stents in congenital heart disease interventions

Abstract: ObjectivesTo evaluate bare-metal Optimus and polytetrafluoroethylene (PTFE)-covered Optimus-CVS balloon-expandable, cobalt–chromium, hybrid cell–designed stents in congenital heart disease (CHD) interventions.MethodsRetrospective multicentre review of patients with CHD receiving Optimus stents. Stent mechanical behaviour, clinical indications and outcomes were assessed.Results183 stents (49.2% XXL/15-ZIG, 33.3% XL/12-ZIG, 17.5% L/9-ZIG) were implanted (98.9% success rate, 2.3% serious procedural complication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Following expansion, the stent adhered well to the vessel wall at the level of the narrowing segment. Despite some procedural and technical advantages of other new-generation endovascular stents ( 11 ), we have selected the CP stent because of the availability in the armamentarium and operators' experience with CP stents. Even though the residual pressure gradient was not optimal, significant control over blood pressure was achieved with medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following expansion, the stent adhered well to the vessel wall at the level of the narrowing segment. Despite some procedural and technical advantages of other new-generation endovascular stents ( 11 ), we have selected the CP stent because of the availability in the armamentarium and operators' experience with CP stents. Even though the residual pressure gradient was not optimal, significant control over blood pressure was achieved with medications.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the residual pressure gradient was not optimal, significant control over blood pressure was achieved with medications. We refrained from further expansion or additional stent placement to avoid the risk of vessel tearing due to excessive expansion ( 11 ). Subsequent follow-up showed that the patient's blood pressure was normalized with medication, supporting the correctness of our comprehensive decision.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Co is present in superalloys, other alloys, heavy metals (cement carbides), magnets, wear-resistant materials, recording materials, batteries, tires, paint dryers, soaps, and catalysts [13]. Recently, Co-chromium balloon-expandable vascular stents have been used in congenital heart disease interventions [14].…”
Section: Introductionmentioning
confidence: 99%